2007
DOI: 10.3171/spi-07/12/615
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of the postoperative evolution of intramedullary spinal cord changes in signal intensity on magnetic resonance imaging after anterior decompression for cervical spondylotic myelopathy

Abstract: Object Areas of intramedullary signal intensity changes (hypointensity on T1-weighted magnetic resonance [MR] images and hyperintensity on T2-weighted MR images) in patients with cervical spondylotic myelopathy (CSM) have been described by several investigators. The role of postoperative evolution of these alterations is still not well known. Methods A total of 47 patients underwent MR imaging before and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 26 publications
1
73
0
Order By: Relevance
“…Some authors reported that patients with ISI have poor prognosis after surgery 2-6 ; however, others found no correlation between surgical outcome and intramedullary high SI on T2WI. [7][8][9][11][12][13] As far as we know, Takahashi et al first reported the MR findings of intramedullary high SI in CSM. They considered intramedullary high SI as an indicator of poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors reported that patients with ISI have poor prognosis after surgery 2-6 ; however, others found no correlation between surgical outcome and intramedullary high SI on T2WI. [7][8][9][11][12][13] As far as we know, Takahashi et al first reported the MR findings of intramedullary high SI in CSM. They considered intramedullary high SI as an indicator of poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the significance of ISI for prognosis remains controversial. [2][3][4][5][6][7][8][9][10][11][12] In this context, the aim of this study is to quantize signal intensity (SI) ratio and to determine whether MR T2 image SI ratio and clinical manifestation can contribute to assess the prognosis of the disease. …”
mentioning
confidence: 99%
“…Duration of preoperative symptoms greater than 12 months has been associated with poorer outcomes [24,25]. Although many authors are not impressed with intramedullary MR changes as a predictor of outcome, some data exists to suggest that T1 hypointensity along with T2 hyperintensity within the cord, particularly if multisegmental, are associated with poor outcomes and probably an irreversible pathology [26,27].…”
Section: Clinical and Radiological Predictive Factorsmentioning
confidence: 99%
“…Similar fi ndings have been described by other authors. 6 , 8 Mastronardi et al , 7 studying 37 patients with intramedullary ISI after anterior cervical discectomy, showed that 12 patients with regression of T2-weighted signal change had improvements in both modifi ed Japanese Orthopaedic Association scores and Nurick grades. Although the presence of persistent focal T2W ISI (similar to type 2 ISI) at 6 months postoperatively has been shown to predict clinical outcome at 1 year, 10 it is unclear if intramedullary MR signal change beyond the fi rst year after surgery is of prognostic value.…”
Section: Clinical Correlates Of Change In Isimentioning
confidence: 98%
“…6 In addition, there are inconsistent data on the clinical correlates of changes in ISI characteristics on postoperative imaging. [7][8][9][10] In this study, we evaluated change in the type of T2W ISI in a series of patients after central corpectomy for CSM or ossifi ed posterior longitudinal ligament (OPLL). We also aimed to determine if a change in ISI postoperatively was associated with functional outcome after surgery.…”
mentioning
confidence: 99%